STRATEGI PEMASARAN BERAS ORGANIK (Studi Kasus Pada Pusat Pelatihan dan Pedesaan Swadaya (P4S) Bale Pare Pertanian Organik di Desa Pasirkaliki, Kecamatan Rawamerta, Kabupaten Karawang). - Maulidya, Nita; Abubakar, Abubakar; Bayfurqon, , Fawzy Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) Bale Pare Pertanian Organik is one of the institutions that develops the organic rice business. The organic rice produced is declared halal and safe for consumption because it has been tested and certified. This has very good potential to be developed, but in the marketing process, it is still not optimal. The purpose of this study is to identify factors such as strengths, weaknesses, opportunities, and major threats, analyze alternative marketing strategies, and determine priority strategies. The research method used is descriptive, with qualitative and quantitative approaches. This study used primary and secondary data. In primary data collection using interview techniques using questionnaires. Respondents in this study consisted of the Chairman of P4S Bale Pare Pertanian Organik, eight farmers at P4S Bale Pare Pertanian Organik who were expected to be key informants, then the Department of Agriculture and Food Security, the Department of Industry and Trade, and two consumers. Secondary data are obtained through literature studies. The sample is taken by purposive sampling. The data analysis of this study used SWOT analysis and the QSPM matrix. The results showed that the main strength is already having halal labels, net, PIRT, expired date, and barcode with a score of 0.31; the main weakness is not yet available in the marketplace with a score of 0.09; the main opportunity is the trend of a healthy lifestyle that increases with a score of 0.26; and the main threat is substitution products (inorganic rice) with a score of 0.23. In the SWOT analysis, nine strategies were obtained, and based on the results of these strategies, a QSPM analysis was carried out so as to produce a strategy that became a top priority, namely increasing cooperation with various related marketing partners to expand the market, with a score of 7.51.